2013
DOI: 10.3329/bjmp.v4i1.14693
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Low Cost Bone Densitometer Based on Conventional X-Ray Facility

Abstract: Osteoporosis or bone loss affects many people, particularly the aged women, and leads to disabling bone fractures. An early diagnosis could provide preventive management. However, available bone densitometry equipment are very expensive and not available widely in the Third World. The present work presents the design & development of an innovative low cost bone densitometer based on conventional X-ray equipment available widely. The main innovation is the incorporation of a stack of aluminium with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…HU units are commonly used to quantify bone mineral density, where measurements are performed using CBCT [27]. On the other hand, Al-Eq unit is another method used to evaluate bone density by comparing the equivalent thickness of aluminium to standard bone density equipment [28]. The qualitative assessment of this study suggested that PRF may provide higher bone density in a longer post-operative course; however, the resorption rate does not differ significantly in both groups at the end of 12 months [16].…”
Section: Discussionmentioning
confidence: 99%
“…HU units are commonly used to quantify bone mineral density, where measurements are performed using CBCT [27]. On the other hand, Al-Eq unit is another method used to evaluate bone density by comparing the equivalent thickness of aluminium to standard bone density equipment [28]. The qualitative assessment of this study suggested that PRF may provide higher bone density in a longer post-operative course; however, the resorption rate does not differ significantly in both groups at the end of 12 months [16].…”
Section: Discussionmentioning
confidence: 99%